PERBANYAKAN DAN PEMATANGAN EMBRIO SOMATIK Pinus merkusii Jungh. & Devr. PADA MEDIUM PAJHJ DCR - Ria Arista, - (2008)
The study on the proliferation and maturation ofPinus merkusii Jungh. & Devr. somatic embryos has been done. The aim ofthis study is to describe the growth of pine ESM on the solid medium and to observed it's maturation response on the DCR medium containing 6%PEG and 0; 2,5; 5; 7,5 and 10 uM ABA. The proliferation ofESM conducted on DCR medium suplemented with 9 uM 2,4-D, 2 fxM BAP, 20 g/L sucrose and 8 g/L agar. Both proliferation and maturation experiment conducted in the dark at room temperature. On proliferation medium different ESM show different growth rate which could be devided into three groups; the fastest (4-5 weeks); the middle (5-6 weeks) and the slowest (7-8 weeks) growth rate groups ofESM. Maturation experiment showed only two clone (PMC 2and PMC 11) of ESM indicating a maturation respons could be observed by the development ofthe embryo from proembryo stage to prekotiledon stage.